PENGATURAN BEBAN KOMPLEMEN LAMPU DAN MOTOR LISTRIK PENGGILING KOPI SEBAGAI PENSTABIL TEGANGAN MENGGUNAKAN MIKROKONTROLER ATMEGA8535 PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO 5 KW (Study Kasus di Desa Talang Jawa Lampung Barat) - Herliansyah, - -; Harahap, Charles R; Raharjo, Yuliarto - (Jurnal Informatika dan Teknik Elektro Terapan, 2013)
Gutters Javanese village is the village where people do not get the energy supply of electricity. People in this area make microhydro power plant, manufacture of power generation because microhydro is supported in this area are river flows from the mountains. In the study microhydro voltage control device is installed on the system controller uses ATmega8535 as the primary device. Installation of the controller circuit is due at microhydro is the case over voltage. Over voltage due to rotor rotation is over, resulting in over voltage at zero load To overcome these problems then be made to serve the load when the load shifted to zero at the expense of consumers. Complement the load is controlled by a microcontroller ATmega8535. Complement the work load placed on the system to reduce the previous voltages 310 volts to 230 volts by regulating the activation of complement load Key words: microhydro, complement Load, Load consumers.